THE EFFECT OF MIXED TEACHING MODE BASED ON NETWORK OPEN COURSE AND INTELLIGENT TEACHING PLATFORM ON ALLEVIATING STUDENTS' PSYCHOLOGICAL ANXIETY - Yin, Xiaoke; Tang, Zhiwei; Abid, Ali (The international journal of neuropsychopharmacology, 2022)
Abstract Background The rapid rise of various new online open courses has brought new opportunities and challenges to China's higher education teaching and teaching management. Classroom teaching in Colleges and universities is the core of the whole teaching activities, which undertakes the important educational objectives of shaping group personality value, cultivating group ability and imparting knowledge. Therefore, how to stimulate the group's interest in classroom teaching has become an urgent problem for college graduates. Under the background of the current “Internet +” era and the construction of “double first-class” universities, how to maximize the use of online open courses to serve the curriculum reform and innovation of colleges and universities, and solve the dilemma of current college education and teaching innovation, has become a new issue facing higher education. Topics and Methods Using modern information technology and integrating online and offline resources will be the trend of higher education teaching reform in the future. A large number of open online courses and related platforms promote the development of various information-based teaching methods, are impacting and affecting the classroom teaching in Colleges and universities, and have a far-reaching impact on the teaching reform and innovation in Colleges and universities. This paper makes full use of all kinds of network open curriculum resources and combined with lightweight intelligent teaching platform, and puts forward a hybrid teaching mode based on network open curriculum and intelligent teaching platform. At the same time, it discusses how to alleviate students' anxiety and depression. The center for flow regulation Depression Scale (CES-D) was used to evaluate the individual's depression level in the last week. There are 20 items in the questionnaire. Likert's 4-point score is adopted. 0 represents “occasionally or none”, 1 represents “sometimes”, 2 represents “often or half the time”, and 3 represents “most of the time or duration”. Four of them are reverse scoring. The total score of the questionnaire is the sum of each item. The greater the total score, the higher the individual's depression level. In the current study, Cronbach's α Is. 83. In this study, the delineation score of CES-D suggested by the latest research was used to screen adolescents without depression, subthreshold depression and depression. Specifically, the researchers measured the depressive symptoms of 5565 Chinese adolescents with the central depression scale (CES-D), and interviewed 634 of them with a total score of CES-D ≥ 20 on the clinical diagnosis of affective disorder and schizophrenia (K-SADS) in school-age children, so as to examine the demarcation score and validity of screening all adolescents with depressive disorder (including mild depressive disorder and depression) with CES-D. The results showed that the total score of CES-D ≥ 24 and ≥ 29 were the best demarcation scores for screening all depressive disorders and depression, with sensitivity of 97% ~ 94%, specificity of 74% ~ 79%, positive predictive value of 30% ~ 21%, and area under receiver operating characteristic (ROC) curve (AUC) of. 88 ~. 91. Because this study not only has the advantages of large sample size and strong timeliness, but also the relevant results have direct reference value for this study, adolescents with CES-D total score < 24 are screened as non depressed adolescents, adolescents with 24 ≤ CES-D total score < 29 are screened as subthreshold depressed adolescents, and adolescents with CES-D total score ≥ 29 are screened as depressed adolescents. Results The teaching mode can push the teaching materials into the hands of students, record the whole process of teaching data, realize the digital management of the whole process of teaching, and adjust the teaching strategy in time. The teaching mode proposed in this paper can make the evaluation of students' learning process more comprehensive, accurate and objective. The traditional student evaluation process is usually carried out through classroom attendance, classroom performance and group submission of homework. This method has strong subjectivity and low quality of students' homework. At the same time, it is difficult to make a comprehensive and accurate evaluation of students. From the perspective of teaching effect, students' anxiety is negatively correlated with their grades. The simple effect analysis of the interaction between the subject group and the strategy type found that the subject group was in the cognitive reappraisal (f (2, 763) = 9.72, P <. 001, η 2 =. 03), cognitive immersion (f (2, 763) = 17.67, P <. 001, η 2 =. 04), expression inhibition (f (2, 763) = 5.63, P <. 01, η 2 =. 02) and expression catharsis (f (2, 763) = 3.96, P <. 05, η 2 =. 01). After comparison, it was found that for cognitive reappraisal, non depressed adolescents were significantly higher than subthreshold depressed adolescents (P <. 05) and depressed adolescents (P <. 001), but there was no significant difference between subthreshold depressed adolescents and depressed adolescents (P >. 05); For cognitive immersion, non depressed adolescents were significantly lower than subthreshold depressed adolescents (P <. 01) and depressed adolescents (P <. 001). However, there was no significant difference between subthreshold depressed adolescents and depressed adolescents (P > 0.05); For expression inhibition, there was no significant difference between non depressed adolescents and subthreshold depressed adolescents (P >. 05), and non depressed adolescents were significantly lower than depressed adolescents (P <. 01), but there was no significant difference between subthreshold depressed adolescents and depressed adolescents (P >. 05); For expression catharsis, non depressed adolescents were significantly lower than subthreshold depressed adolescents (P <. 05) and depressed adolescents (P <. 05), but there was no significant difference between subthreshold depressed adolescents and depressed adolescents (P >. 05). Conclusion Through the practice of specific courses, the results show that the teaching model can effectively mobilize students' learning interest and improve the teaching effect and efficiency. As an important breakthrough in the reform of higher education in the future, online open curriculum can reconstruct the service mode of higher education, improve students' autonomous learning ability and cultivate students' ability to adapt to the new era of innovation. Make full use of online open courses at home and abroad and famous teacher courses in well-known universities to find teaching materials suitable for their students, absorb the excellent teaching achievements of others, apply them to classroom teaching, and guide students to carry out autonomous learning and in-depth learning in an appropriate way. Acknowledgements Supported by a project grant from “Theory and Practice project of Vocational Education Highland Construction in Hunan Province in 2021 ”Research on Hybrid Teaching Mode Based on Online Open Courses and Intelligent Teaching Platform“ (Project No. ZJGD2021237)